The self concept of sixth form and first year university students / Wong Lai Sum - Wong, Lai Sum (1977)
This study investigates the relationships of the cognitive and the affective components of self concept with three variables namely, sex, race, and academic level, and their interactions. Academic Self Concept, the cognitive component, was measured by the Brookover Self Concept of Ability Scale while Self Esteem and its five subscales, the affective component, was measured by the Tennessee Self Concept Scale. The sample consisted of 120 subjects which was equally divided into University and Sixth form groups. Each of these was further divided into groups of Malays and Chinese, each of which was in turn subdivided into groups of males and females. Tha findings included the following:- (a) No significant sex differences were found in any of the components of the Self Concept studied. (b) Significant race differences in Social Self ware found for the Sample with the Chinese scoring higher than the Malays. (c) Significant race differences in Academic Self Concept were found far the Sixth formers only, with the Chinese scoring higher than the Malays. (d) Significant academic level difference in family Self were found for tho Sample with the University group scoring higher then the Sixth formers. (e) Sex and race interacted significantly to affect scores in Physical Self for the Sixth formers only.